"From warfare to welfare": Contextualising Arrow and Schelling's models of racial inequalities (1968–1972)*. Issue 6 (2nd November 2017) - Chassonnery-Zaïgouche, Cléo; Larrouy, Lauren
ABSTRACT: This paper focuses on Arrow and Schelling's contributions to the study of racial inequality in the late 1960s. We start from the authors' account of the origin of their work. Then, we locate the "material origin" of the models at the RAND Corporation in the late 1960s and show how it relates to the transfer of the RAND tool-box to the study of welfare issues. Finally, we describe how Arrow's and Schelling's modelling strategies relate to their conception of "science for action, " inherited from their "warfare" work.